Halloween windstorm and tornadoes in England, 31 October 2021. (3rd February 2022) - Holley, Dan
Abstract : During the morning of Sunday 31 October 2021, damaging winds affected a corridor from Dorset through the south and east Midlands to Lincolnshire, associated with a mesolow that developed along a cold front. Hundreds of trees were damaged or blown over, bus and train services were significantly disrupted and numerous buildings were also impacted. Provisional analysis by TORRO suggests at least eight confirmed tornadoes, and an additional six probable tornadoes, occurred within the much larger field of wind damage.